A new species of hydrothermal vent stalked barnacle Vulcanolepas (Scalpelliforms: Eolepadidae) from the North Fiji Basin, Southwestern Pacific Ocean - Chan, Benny K.k.; Ju, Se-Jong; Kim, Se-Joo (Zootaxa, 2019)
A new species of eolepadid stalked barnacle, Vulcanolepas fijiensis sp. nov., was collected from a hydrothermal vent in the North Fiji Basin, Southwestern Pacific Ocean, at a depth of 1988 m. Based on morphological characteristics, this new species was distinguished from its relatives, V. osheai Buckeridge, 2000, V. parensis Southward, 2005, V. scotiaensis Buckeridge, Linse & Jackson, 2013, and V. buckeridgei Chan & Chang, 2018. Based on morphological characteristics, Vulcanolepas species are divided mainly into two groups by the size of the first mandibular tooth; the first group has a large mandibular first tooth (V. parensis, V. scotiaensis, and V. fijiensis sp. nov., the second a small mandibular first tooth (V. osheai and V. buckeridgei). The new species can be easily distinguished from V. parensis and V. scotiaensis by the length ratio of antenniform segments to robust segments of the rami of cirrus I. Vulcanolepas fijiensis sp. nov. also differs from V. parensis by the length ratio of the penis and cirrus VI (1/10 vs 1/4), and the extension the carinal apex to the tergum (extended vs not extended). Additionally, the sequence divergence of the cytochrome c oxidase 1 gene between V. fijiensis sp. nov. and the other neolepadid species (except V. parensis from its original locations) ranged from 4.2% to 14.0%. In a neighbor-joining tree, V. fijiensis sp. nov. formed an independent branch. These results infer that V. fijiensis sp. nov. is a new species, distinct from the other known neolepadids.